Introduction: Representations in The Creative Arts of Southeast Asia, Negotiating Meanings and Identities - Tan Sooi Beng (Wacana Seni Journal of Arts Discourse, 2012)
This collection of articles highlights issues related to the representation of social meanings and identities in the production and reception of the creative arts in the Philippines, Indonesia, Malaysia, Singapore, Thailand and Burma. The articles illustrate that the creative arts are sites of dialogue which articulate diverse meanings to different audiences. They are forms of representation which generate new identities and provide spaces for artistes to speak. Artistes become agents of change as they negotiate their identities and respond to larger social issues and forces such as gender, ethnicity, modernity, nation building, migration, global flows of culture, militarism and authoritarianism. The articles exemplify ways of negotiating the dominant modes of power that prevail in Southeast Asia.